Universality of the right to health and material equality: economic and social inequalities and inequalities in health - Dalli Almiñana, María (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2015)
This work will defend the universality of the right to health, against the postures that deny that social rights are universal, and that still remain in doctrinal positions and in the current legal regulation of the right to health. The idea of ‘charity’ will be referred, in relation to the ‘affordability’, as well as the administrative status requirement for the enjoyment of the rights, in connection with the Spanish legislation that regulates the access to the National Healthcare System. On the other hand, the universality in relation to the material equality goes against the social inequalities in health, demonstrating differences in health opportunities between people. Likewise, the economic and social inequality between sectors of a population has been analysed as a detrimental factor for the health indicators of societies.